Overactivity of Alternative Pathway Convertases in Patients With Complement-Mediated Renal Diseases - Michels, Marloes A. H. M.; van de Kar, Nicole C. A. J.; Okrój, Marcin; Blom, Anna M.; van Kraaij, Sanne A. W.; Volokhina, Elena B.; van den Heuvel, Lambertus P. W. J. (Frontiers in Immunology, 2018)
Overactivation of the alternative pathway of the complement system is associated with the renal diseases atypical hemolytic uremic syndrome (aHUS) and C3 glomerulopathy (C3G). C3 nephritic factors (C3NeF) play an important role in C3G pathogenesis by stabilizing the key enzymatic complex of complement, the C3 convertase. However, the reliability of assays detecting these autoantibodies is limited. Therefore, in this study we validated and optimized a prototype hemolytic method for robust detection and characterization of factors causing convertase overactivity in large patient cohorts. The assay assesses convertase activity directly in the physiological milieu of serum and therefore is not restricted to detection of stabilizing autoantibodies such as C3NeF, but may also reveal genetic variants resulting in prolonged convertase activity. We first defined clear cut-off values based on convertase activity in healthy controls. Next, we evaluated 27 C3G patient samples and found 16 positive for prolonged convertase activity, indicating the presence of factors influencing convertase stability. In three patients, the overactive convertase profile was persistent over disease course while in another patient the increased stability normalized in remission. In all these four patients, the convertase-stabilizing activity resided in the purified immunoglobulin fraction, demonstrating the autoantibody nature. In contrast, the immunoglobulins of a familial aHUS patient carrying the factor B mutation p.Lys323Glu did not reveal convertase stabilization. However, in serum prolonged convertase activity was observed and segregated with the mutation in both affected and unaffected family members. In conclusion, we present a robust and reliable method for the detection, characterization, and evaluation over time of factors prolonging convertase activity (C3NeF or certain mutations) in patient cohorts. This assay may provide new insights in disease pathogenesis and may contribute to the development of more personalized treatment strategies.